A Study Protocol on the Evaluation of Comparative Efficacy of Waj (Acorus calamus Linn.) versus Pregabalin in Diabetic Peripheral Neuropathy - Shahid, Mohd; Quamri, Mohd Aleemuddin (International Research Journal of Ayurveda & Yoga, 2024)
Background: Diabetes is a major global health concern in the twenty-first century. The International Diabetes Federation (IDF) estimates that by the end of 2021, complications from diabetes would have killed 747,000 peoples in India. Diabetic peripheral neuropathy (DPN) is a disorder that develops in patients with diabetes (type 1 and type 2) and is not attributable to any other peripheral neuropathy causes. Clinically, it may manifest as burning, tingling, numbness, or neuropathic pain in the foot that tends to get worse at night. DPN frequently results in ulceration, infection, deterioration of the skin, and ultimately amputation. Methods: This study will be conducted as randomized standard-controlled, single-blind trial on 150 DPN subjects with type 2 diabetes by randomly assigned them to two groups (test or standard), where test group will receive two capsules twice (containing 500 mg powder of test drug in each capsule) with water and control group will receive one capsule of pregabalin 75 mg twice. Both groups will be treated for 60 days with 30 days post treatment follow-up addition to their regular anti-diabetic treatment. The subjective parameters of burning, tingling, and pain in the feet will be evaluated every two weeks using the visual analog scale (VAS) and arbitrary scale. Objective parameters, Toronto Clinical Scoring System (TCSS) will be assessed fortnightly along with vibratory perception threshold (VPT), assessed pre and post-treatment. Data will be assessed statistically with appropriate tests.